Intercultural Theology as In-Between Theology - Wrogemann, Henning (Vox Scripturae - Revista Teológica Internacional, 2024)
Since the beginning of the 21st century, the term intercultural theology has been gaining more and more traction. At the same time, the terms world Christianity and anthropology of Christianity have also become established. This article inquires into the profile of intercultural theology against the other two terms and defines the subject as in-between theology with Regard to such factors as audience, media, power, methodology, plurality, and connectivity. Looking forward, the author identifies current challenges and proposes that intercultural theology should be understood as a both descriptive and normative discipline, that the driving force behind it is the universal-missionary truth claim of the New Testament message of salvation, and that—as a subject with a primarily systematic orientation—it is committed to a comprehensive understanding of reality and theology.